Promising Diagnostic Markers of Colon Cancer - S. V. Volkov; S. L. Lobanov (Acta Biomedica Scientifica, 2021)
Background. The incidence of colon cancer over the past decade has been growing markedly in the Russian Federation, with about 50 % cases detected at stagesIII–IV of the disease, when a clear clinical picture of the disease appears. In this regard, the search for new methods for early diagnosis of RTK is undoubtedly relevant.Objective. To determine the standard composition of the aerobic parietal colon microbiota and the level of cytokines (chemokines and growth factors) in patients with cancer of the left half of the colon and to assess the possibility of using these data in the diagnosis of the tumor process.Materials and methods. Blood tests were performed on the day of the study using two test systems (BioLegend): multiplex kit for determining growth factors, chemokine multiplex kit. The composition of the intestinal microbiota was determined in colon biopsy specimens by the bacteriological method using the standard test systems StaphyTest, StreptoTest, and EnteroTest.Results. There is an increase in the number of Clostridiumspp. and a decrease in Bifidobacteriumspp., E. coli in the colon during the transformation of a healthy person’s mucosa into a malignant tumor (p < 0.05); a clear tendency was revealed for both an increase (EGF, HGF, M-CSF, PDGF-AA, PDGF-BB, IP-10) and a decrease (MCP-1, RANTES) of the level of chemokines and growth factors under colon cancer conditions. In addition to general quantitative changes in the intestinal microbiota, the level of the investigated substances, a statistically significant dependence was established on the sex, age of the patient, as well as the degree of differentiation and form of tumor growth.Conclusion. It was established that changes in the quantitative composition of the intestinal microbiota, the level of some biologically active substances that occur precisely in the conditions of colon cancer, can be interconnected and interdependent, and also serve as an additional diagnostic marker in the detection of a malignant tumor.